2013
DOI: 10.1002/bit.25015
|View full text |Cite
|
Sign up to set email alerts
|

Liquid films on shake flask walls explain increasing maximum oxygen transfer capacities with elevating viscosity

Abstract: In biotechnological screening and production, oxygen supply is a crucial parameter. Even though oxygen transfer is well documented for viscous cultivations in stirred tanks, little is known about the gas/liquid oxygen transfer in shake flask cultures that become increasingly viscous during cultivation. Especially the oxygen transfer into the liquid film, adhering on the shake flask wall, has not yet been described for such cultivations. In this study, the oxygen transfer of chemical and microbial model experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 62 publications
2
29
0
1
Order By: Relevance
“…Previous liquid culture studies showed that increasing medium viscosity increased dissolved oxygen levels (Giese et al, 2013;Mascarin et al, 2015). Giese et al (2013) demonstrated that high-viscosity media tend to adhere to the flask wall, thus increasing oxygen transfer by increasing the surface area of the medium. In our case, it may be that agar's role in integration of the oil phase into the liquid medium may also have improved oxygen transfer by increasing exposure of the medium to air.…”
Section: Discussionmentioning
confidence: 96%
“…Previous liquid culture studies showed that increasing medium viscosity increased dissolved oxygen levels (Giese et al, 2013;Mascarin et al, 2015). Giese et al (2013) demonstrated that high-viscosity media tend to adhere to the flask wall, thus increasing oxygen transfer by increasing the surface area of the medium. In our case, it may be that agar's role in integration of the oil phase into the liquid medium may also have improved oxygen transfer by increasing exposure of the medium to air.…”
Section: Discussionmentioning
confidence: 96%
“…Figure (c) shows a simulation of the apparent viscosity performance estimated from n and k values, assuming a shear stress value of 300 s ‐1 . The γ value of 300 s ‐1 used in this work for the η estimations was previously found to be the mean shear rate at the usual operating conditions in orbital shake flasks . The highest apparent viscosity of 15.47 ± 6.93 mPa.s was achieved by the cultures grown at 20 g , whereas at 5, 10, and 15 g , values of 3.03 ± 0.18, 5.22 ± 0.42, and 1.26 ± 0.03 mPa.s were obtained, respectively.…”
Section: Resultsmentioning
confidence: 76%
“…As shown previously, RAM is able to achieve higher k L a values;, therefore, higher OTR max are expected than those typically observed in orbital shake flasks. The maximum OTR for the RAMbio system has not been measured yet, but an approximate estimation can be made by using the k L a values from a previous experimental model and by assuming 0.21 mmol L ‐1 (culture medium) as the oxygen concentration at the water–air interface . This estimation gives us maximum OTR values between 11.0 and 49.7 mmol L −1 h −1 for the 500 mL flasks used with 100 mL of culture medium at shaking frequencies between 5 and 20 g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sua disponibilidade é dependente da transferência de oxigênio do ambiente para o líquido, a qual é incrementada com o uso de Erlenmeyer baffled cell culture flasks, altas velocidades de agitação, baixo volume de cultura no frasco (50 mL) e maior viscosidade do meio 2015b). Maiores concentrações de carbono atuam justamente sobre a viscosidade do meio, tornando-o mais viscoso, e um meio com tal característica tende a aderir mais facilmente à parede do frasco, aumentando a transferência de oxigênio para o meio pelo incremente da superfície de contato (GIESE et al, 2013). Em um sistema de retro-alimentação positiva, o crescimento de blastosporos, em detrimento de hifas, melhora a transferência de oxigênio em culturas de fungos (PETER et al, 2004;ISSALY et al, 2005;JACKSON, 2012).…”
Section: Produção Via Fermentação Líquidaunclassified